Heat transfer performance of a self-oscillating heat pipe using pure water and effect of inclination to this performance. - Tung, Dao Danh (Asean Engineering Journal)
This experimental study is performed to investigate heat transfer performance and effect of inclinations to a self-oscillating heat pipe developed. In this experiment, pure water is employed as the working fluid.